Experimental and Numerical Study of the Trench Fire Spread Rule over a Sloped Uniform Fuel Bed: Rate of Fire Spread, Flame Morphology, and Heat Flux - Yi Wang; Rui Huang (Fire, 2023)
Trench fires on sloped terrain are always complicated due to the corresponding flame dynamics and heat transfer mechanisms. Flame attachment may increase the rate of fire spread (ROS) by enlarging the heating area of unburned vegetation. In addition, variations in radiative and convective heat flux are of great importance to fire behavior characteristics. In this work, trench fire tests under different slopes (θ) and inclined sidewalls (A) were performed by numerical simulations based on the Lagrangian Particle Model (LPM) and Boundary Fuel Model (BFM) in the Fire Dynamics Simulator (FDS) and small-scale experiments, and the ROS, flame characteristics, and radiative/convective heat flux of the fire front are discussed in detail. The results indicate that the flame tends to adhere to the fuel bed with increasing slope angle and sidewall inclination. In particular, the flame becomes fully attached with a greater pressure difference than the buoyancy, which is caused by the unequal air entrainment between the front and behind the flame. When A = 90°, the critical slope angle of the flame adhesion (from slight tilt to full attachment) is identified as ~20°. The ROS (θ ≤ 15°) predicted by the BFM and LPM are closer to the small-scale experiments. The heat fluxes based on the experiments confirm the predominant mechanism of radiative heat transfer in trench fires at low slopes (θ ≤ 20°). Furthermore, convective heat transfer is more significant than radiative and becomes the main heating mechanism for θ ≥ 20°.